PENGARUH PERSEPSI KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KREATIVITAS DOSEN DENGAN EFIKASI DIRI KREATIF SEBAGAI PEMEDIASI - Elfitra Azliyanti; Purbo Jadmiko; Wiry Utami (Jurnal Apresiasi Ekonomi, 2020)
AbstractThis study aims to identify and analyze the role of perception of transformational leadership and creative self-efficacy of employee (lecturer) creativity. The research methodology used is explanatory research through hypothesis testing. The object and population of this study are Bung Hatta University Lecturers. The sampling technique used was purposive sampling with sample criteria was Bung Hatta University Lecturer who had working period  more than 1 (one) year (n = 170). The data analysis technique in this study use SEM-PLS (Smart PLS). This study consists of three hypotheses and the research results obtained from the study of perceptions of transformational leadership has no effect on employee creativity, Creative self-efficacy has a positive effect on employee creativity and creative self-efficacy mediates the relationship of perception of transformational leadership on employee creativity.Keywords : perception of transformational leadership, employee creativity , Creative self-efficacy